International investment law the sources of rights and obligations - Gazzini, Tarcisio; Brabandere, Eric de (BRILL, 2012)
Drawing on State practice, arbitral awards and national decisions, this book provides a systematic study of the sources of rights and obligations in the field of transnational investment, and their coordination and interaction.